MANAGEMENT OF TRAINING SPECIALISTS IN INTELLECTUAL PROPERTY: PRESENT STAGE TRANSFORMATIONS - Lazarev M.I.; Lunyachek V.E.; Ruban N.P.; Timaniuk V.M.; Fesenko N.S.; Chernenko Yu.Yu. (Pressing Problems of Public Administration, 2017)
The paper considers genesis of the management process of training specialists in the  eld ofintellectual property at the higher educational institutions of Ukraine as a prerequisite for furthereconomic development. Emphasis is placed on the economic signi cance of the process associatedwith the intellectual property commercialization, which directly affects the GDP growth within theknowledge-based economy.